The Animal-Visitor Interaction Protocol (AVIP) for the assessment of Lemur catta walk-in enclosure in zoos - Pollastri, Ilaria; Normando, Simona; Florio, Daniela; Ferrante, Linda; Bandoli, Francesca; Macchi, Elisabetta; Muzzo, Alessia; de Mori, Barbara (PLOS ONE, 2022)
Animal–Visitor Interactions (AVI) are activities offered by zoos and other tourism facilities, in which visitors come into close contact with animals. These activities can promote conservational and educational content, raise conservation mindedness and responsibility for the environment and animal welfare, but if not properly managed can jeopardize visitors’ and animals’ well-being and conservation efforts. The Animal-Visitor Interaction assessment Protocol (AVIP) has been designed to perform an integrated and multidisciplinary assessment of these activities, encompassing the “One Health, One Welfare” approach. AVIP throughout six different steps allows to assess the effects of AVIs both on animals, visitors, and the staff involved. Results can assist zoos to improve management decisions, ensure a transparent evaluation of their activities and promote conservation education goals. Lemurs walk-in enclosures have become increasingly popular among zoos, nevertheless studies focused on their assessment are still scarce. To validate AVIP to this particular AVI, we applied it to assess a walk-in enclosure hosting five Lemur catta in an Italian zoo. Results of behavioural and physiological analyses suggested no changes in animal welfare level and the Animal Welfare Risk Assessment showed low animal welfare risks. Two Visitor Experience Surveys were used to interview 291 visitors, showing that the assessed AVI could help promote the zoo’s conservation objectives and visitor education. Risk Assessment found low and medium risks to the health and safety of visitors. Results were then combined to perform a final ethical assessment. Some potential ethical concerns were detected, but the outcomes indicated that these conflicts were well managed. In the context of recent findings AVIP demonstrated its potential for application also in assessing AVIs involving primates. Our findings confirmed the usefulness of AVIP in assessing and monitoring AVIs, allowing to gain key information in a single process on multiple welfare-related parameters, educational impact, safety of the main stakeholders involved, and ethical concerns.